If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3a + 43)(2a + 37) = 0 Reorder the terms: (43 + 3a)(2a + 37) = 0 Reorder the terms: (43 + 3a)(37 + 2a) = 0 Multiply (43 + 3a) * (37 + 2a) (43(37 + 2a) + 3a * (37 + 2a)) = 0 ((37 * 43 + 2a * 43) + 3a * (37 + 2a)) = 0 ((1591 + 86a) + 3a * (37 + 2a)) = 0 (1591 + 86a + (37 * 3a + 2a * 3a)) = 0 (1591 + 86a + (111a + 6a2)) = 0 Combine like terms: 86a + 111a = 197a (1591 + 197a + 6a2) = 0 Solving 1591 + 197a + 6a2 = 0 Solving for variable 'a'. Factor a trinomial. (37 + 2a)(43 + 3a) = 0Subproblem 1
Set the factor '(37 + 2a)' equal to zero and attempt to solve: Simplifying 37 + 2a = 0 Solving 37 + 2a = 0 Move all terms containing a to the left, all other terms to the right. Add '-37' to each side of the equation. 37 + -37 + 2a = 0 + -37 Combine like terms: 37 + -37 = 0 0 + 2a = 0 + -37 2a = 0 + -37 Combine like terms: 0 + -37 = -37 2a = -37 Divide each side by '2'. a = -18.5 Simplifying a = -18.5Subproblem 2
Set the factor '(43 + 3a)' equal to zero and attempt to solve: Simplifying 43 + 3a = 0 Solving 43 + 3a = 0 Move all terms containing a to the left, all other terms to the right. Add '-43' to each side of the equation. 43 + -43 + 3a = 0 + -43 Combine like terms: 43 + -43 = 0 0 + 3a = 0 + -43 3a = 0 + -43 Combine like terms: 0 + -43 = -43 3a = -43 Divide each side by '3'. a = -14.33333333 Simplifying a = -14.33333333Solution
a = {-18.5, -14.33333333}
| x^2-3x+2=1 | | 17.6-18.28=21.8n-41.8 | | 2/3m-1/2=3/5 | | x^2-6x=-12 | | 4(5a-3)-3(2a-5)=17 | | tan12=100/x | | -4y-2y+8=0 | | r/r^-5*r^-4 | | 20x-3=8x+105 | | (2/3)x-18=(x/8) | | y=0.8sinx | | 3.4+x=20.9 | | 4x+3-3=23-3 | | 3(2x+4)=(3x+4)+4 | | 0.12/4.80= | | 2x-3y+5-(x-3y)=11-2x | | 3(2x+4)=(3x+5)+4 | | .12(x)=40 | | 4.8/.12=40 | | 3(x+5)=2+3x | | 4.8/.12= | | 3x^2+13x+19=0 | | 10x+14y=6072 | | 4.8/.12 | | 3(2x+4)=(3x+3)+6 | | (2-v)(4v+7)=0 | | 3x+2y-x-y+xy= | | 260x(=360/4) | | 4.5x+4=3.5x | | 9a^3/-3a | | 3(2x+4)=2(3x+4) | | 169=81x^2 |